2014
DOI: 10.1099/ijs.0.066688-0
|View full text |Cite
|
Sign up to set email alerts
|

Description of Comamonas serinivorans sp. nov., isolated from wheat straw compost

Abstract: A Gram-stain-negative bacterium, designated SP-35T, was isolated from compost and was subjected to a taxonomic study. This isolate was short-rod-shaped and non-spore-forming. Phylogenetic analysis based on 16S rRNA sequence comparison indicated the isolate was related to the genus Comamonas . 16S rRNA gene sequence analysis showed that its closest neighbours were the type strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…The cellular length and diameter for the used bacterial models are as follows: Comamonas 0.6-0.8 mm and 0.8-2.0 mm (Zhu et al, 2014), Nitrosomonas europaea 1.2-1.7 mm and 1.0-1.2 mm (Meiklejohn, 1950), and Nitrobacter winogradskyi has 0.5 mm and 1.0 mm, respectively (Zavarzin and Legunkova 1959). These were homogenized and simplified as a Stoke's diameter of 5.6 • 10 -5 cm.…”
Section: Activity Testsmentioning
confidence: 99%
“…The cellular length and diameter for the used bacterial models are as follows: Comamonas 0.6-0.8 mm and 0.8-2.0 mm (Zhu et al, 2014), Nitrosomonas europaea 1.2-1.7 mm and 1.0-1.2 mm (Meiklejohn, 1950), and Nitrobacter winogradskyi has 0.5 mm and 1.0 mm, respectively (Zavarzin and Legunkova 1959). These were homogenized and simplified as a Stoke's diameter of 5.6 • 10 -5 cm.…”
Section: Activity Testsmentioning
confidence: 99%
“…from the casing material for Agaricus bisporus. Zhu et al (2014) found Comamonas serinivorans sp. nov. in wheat straw compost.…”
Section: Discussionmentioning
confidence: 99%
“…are basically aerobic but it has been reported that one species is weakly positive for nitrate reduction (Yang et al 2014). Comamonas serinivorans is a facultative anaerobe capable of nitrate reduction (Zhu et al 2014). Petrimonas mucosa is a facultative anaerobe that uses fermentation under anaerobic conditions (Hahnke et al 2016).…”
Section: Phylogenetic Analysis Of the Dominant Otusmentioning
confidence: 99%